Dekarbonisasi Kepemimpinan: Peran Direktur SDM dalam Mengintegrasikan Rendah Karbon ke dalam KPI Kinerja dan Kepemimpinan - Mochammd Rifki Afriansyah; Wildan Fuady; Mohammad Sya’bani Rakhmatulloh; Mochammad Isa Anshori (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
Climate change has encouraged corporations to establish carbon emission reduction targets as part of their sustainability strategies. However, achieving these targets depends not only on technological innovation and operational policies but also on an organization's ability to integrate decarbonization agendas into human resource management systems. This study aims to analyze the strategic role of Human Resource Directors in integrating corporate carbon emission reduction targets into employee performance management systems and leadership Key Performance Indicators (KPIs). This research employs a qualitative approach using a systematic literature review by examining various relevant scientific publications related to Strategic Human Resource Management, Green Human Resource Management, and performance management within the context of organizational sustainability. The analysis process was conducted through systematic literature selection, mapping of previous research findings, and thematic synthesis of concepts and relationship patterns identified in the literature. The findings indicate that the integration of carbon emission targets into organizational performance management systems can be implemented through sustainability-based leadership KPIs, the application of Green HRM practices, and the alignment of employee evaluation and incentive systems with corporate decarbonization objectives. This study contributes to expanding the understanding of decarbonizing leadership by positioning HR Directors as strategic actors who connect corporate sustainability policies with organizational performance management practices, thereby encouraging organizational behavioral transformation toward more sustainable business practices.